MEMBANGUN GENERASI LITERASI DENGAN PEMANFAATAN TAMAN BACA PADA TK ABA 27 KOTALAMA - Muslikhati, Muslikhati (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2020)
Purpose of the study: Adding a reading garden facility to broaden the knowledge of the younger generation (early childhood education) by enriching literacy in the school environment. Methodology: The targets and outputs expected from this service activity are products which can be detailed as follows: a). A banner in the form of Reading Park which will be installed on the room that has been designated as a reading corner or reading garden for TK ABA 27 Kotalama, b). Availability of reading books that support and attract the reading interest of TK ABA 27 students, c). The awakening of interest in reading in early childhood, starting from an interest in reading materials that are preferred, such as moral stories and introduction to the world of animals and other living things, d). Products in the form of reports. Main Findings: Addition of reading garden facilities to broaden the knowledge of the younger generation (early childhood education). Applications of this study: Addition of reading garden facilities. Novelty/Originality of this study: Based on the background above, the focus of this service program is the addition of a reading garden facility to broaden the knowledge of the younger generation (early childhood education).